Pre-Lithiation of Carbon Anodes Using Different Lithium - Sources. (7th July 2017) - Shellikeri, Annadanesh; Watson, Venroy George; Adams, Daniel Lawrence; Kalu, Egwu Eric; Read, Jeffrey A.; Jow, T Richard; Zheng, Jim P.
Abstract : Energy storage devices like batteries and supercapacitors have become indispensable in portable devices and electric vehicles. But the carbon anodes, which exhibit a significant loss in their initial capacity due to consumption of Li ions from electrolyte during SEI layer formation, have the potential to diminish this advantage, if unaddressed. Pre-lithiation treatment of carbon anodes can mitigate this loss, apart from improving the cell working potential, hence enhancing cell energy density and cyclability. We investigate in this report a direct-contact lithiation process in different carbon anodes using various lithium source structures. The results of this study reveal that the type of Li-source structure can have a major impact on the electrode physical properties, pre-lithiation times and the pre-lithiation capacities achieved, effecting the properties of the SEI formed and the electrode processing costs.